2020
DOI: 10.2147/rru.s245669
|View full text |Cite
|
Sign up to set email alerts
|

<p>The Management of Patients Diagnosed with Incidental Prostate Cancer: Narrative Review</p>

Abstract: 5-14% of patients underwent surgery for benign prostate hyperplasia harboring prostate cancer (PCa) focus. The best management of incidental prostate cancer (iPCa) has been debated. The decision "treatment or no treatment" should be determined by predictors which accurately foretell PCa progression after transurethral resection of the prostate (TURP). The purpose of this study is to review the available data that can be useful in daily clinical judgment. Transrectal ultrasound prostate biopsy (TRUSBx) did not … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
16
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 57 publications
0
16
0
1
Order By: Relevance
“…Although there is evidence that the iPCa detection rate fell from 31% to 5.4% through PSA screening, one can expect to detect iPCa after BPH surgery in older men (Bhojani et al, 2015;Elkoushy et al, 2015). The incidence of iPCa after TURP has been reported to range from 5% to 14% (Abedi et al, 2020). Regarding the studies we reviewed, the rate of iPCa after HoLEP ranges between 5.64% and 23.3%.…”
Section: Discussionmentioning
confidence: 93%
“…Although there is evidence that the iPCa detection rate fell from 31% to 5.4% through PSA screening, one can expect to detect iPCa after BPH surgery in older men (Bhojani et al, 2015;Elkoushy et al, 2015). The incidence of iPCa after TURP has been reported to range from 5% to 14% (Abedi et al, 2020). Regarding the studies we reviewed, the rate of iPCa after HoLEP ranges between 5.64% and 23.3%.…”
Section: Discussionmentioning
confidence: 93%
“…Various studies have reported that T1b stage IPCs have a worse prognosis than those at T1a stage [13]. The decision "treatment vs no treatment" is judged by life expectancy, tumor characteristic in the pathology report of TUR-P specimen and PSA level following TUR-P [21]. In light of this information, detailed histopathological and clinical evaluations can be considered of great importance to be able to make a correct diagnosis and for the formation of appropriate follow-up and treatment plans.…”
Section: Discussionmentioning
confidence: 99%
“…Incidental detection of malignancy at the time of HoLEP ranges from 5% to 13% in men without a prior diagnosis of PCa, and there is evidence PSA has improved sensitivity for cancer progression in the post‐HoLEP setting 6–9 . The management of T1a‐b PCa incidentally discovered after transurethral resection of prostate (TURP) has been well documented with AS recommended for the majority of patients 10–12 . However, the management of men with known low‐risk PCa, clinically significant LUTS, and significantly enlarged prostates remains underexplored.…”
Section: Introductionmentioning
confidence: 99%